Postsurgical Pyoderma Gangrenosum Requiring Plastic Surgical Intervention: A Practical Review - Guliyeva, Gunel; Janis, Jeffrey E. (Plastic and reconstructive surgery. Global open, 2024)
Pyoderma gangrenosum is a neutrophilic dermatosis characterized by immune dysfunction and pathergy. Thus, it is frequently seen in patients with underlying systemic illnesses or postoperatively. For the performance of the debridement or closure of the resultant defect, plastic surgeons are often involved in the care of pyoderma patients. However, both procedures may exacerbate the injury. Therefore, plastic surgeons must be familiar with the presentation of postsurgical pyoderma to avoid further damage and safely repair related soft tissue defects. A systematic search of the PubMed/Medline database was performed using the following keywords: "pyoderma gangrenosum" and "surgery." This online database search has identified 656 studies published between 1958 and 2022. Only reconstructed cases of postsurgical pyoderma gangrenosum were selected. Twenty-eight patients who developed pyoderma after dermatologic, plastic, orthopedic, cardiovascular, general, or obstetric surgery were included in this study. The average time to the PG presentation and diagnosis was 5.5 and 17 days, respectively. Diagnostic scoring tools were not used, and the diagnosis was primarily based on histopathology after repeated treatment failures. The patients received split- or full-thickness skin grafts, local, pedicled, and free flaps. An estimated 82.1% underwent skin grafting, whereas 42.9% underwent flap reconstruction. In addition, 21.4% got both the graft and flap. Accurate diagnosis of PSPG, prevention of further surgical injury, and timely medical management are vital for improving patient outcomes. Reconstruction can be performed, if required. However, despite the availability of different reconstructive techniques, there is no standard approach to the management of the PSPG.